MEMBANGUN SERVER BERBASIS LINUX PADA JARINGAN LAN DI LABOR SISTEM INFORMASI JURUSAN TEKNOLOGI INFORMASI POLITEKNIK NEGERI PADANG - Rasyidah, Fifi (Department of Informatics Engineering, 2014)
The System Information Laboratory of Information Technology Department Polytechnic State of Padang has 30 units computer as education facilities to support learning process. All of computers used at same time in a learning section. This case causing trouble to monitoring each students activities. In order to get the solution for the lecturer, the writer then construct a server by using Linux operation system and client by using windows system operation in which Samba File Server is needed. By using this samba, the lecturer will be able to share the data and will be able to use the server as data storage media. Besides that, the writer will also use VNC (Virtual network connection) to simplify the process of monitoring and supervising client working system. Based on the result gotten after the writer done some experiment, it can be concluded that Samba File Server can also be used after some configuration is applied on certain files. Moreover, the writer also conclude that VNC can control the entire of the client. The writer suggests that Samba File server which will be used is the latest version one which has more feature than the previous one, it is suggested that the configuration of VNC is applied on Ubuntu Linux since the service is available. Kata Kunci : Samba File Server, VNC, Ubuntu installation